Ulayat Rights on Presepective Customary Law - Arrahman, Nicolas (Jurnal Scientia Indonesia, 2019)
The implementation of Customary Law in Customary Law is increasingly critical, in the phenomenon of customary law, Ulayat Rights as stipulated in the UUPA Article 3 states "customary rights and similar rights and rights of indigenous and tribal peoples are still implemented by indigenous and tribal peoples as long as the ulayat right is still there. In this article more clearly it is said that the existence of customary rights still exists if its ulayat rights still exist. But it becomes critical because the existence of UUPA in this case is not as strong as the Constitution which became the basis of the State of Indonesia. The law says that the recognition of customary rights is limited to the ulayat right that is still in tune with the development of the era and civilization as Article 28I of the 1945 Constitution.